Does Government Accounting Information Matter to Gain Votes? Evidence from Local Elections in Indonesia - dyah purwanti (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2023)
Voting decisions have become a strategic tool to analyze whether voters consider an incumbent's economic policies make it worthwhile re-electing the incumbent. If a strong correlation between the information on economic policies and the election results could be proved, evidence would thus be found that government accounting captures data on the attributes of government finances, consistent with the information incorporated by constituents in their voting decisions. This study investigates the association between government accounting information and local election outcomes and observes two regional government clusters that held local elections in 2017 and 2018, in which 198 incumbents ran for office again. By employing regression analysis, this study finds that several accounting information items impact the vote acquisition of the incumbents. The specific finding is that budget accounting information has a more decisive influence on votes for the incumbents than financial accounting information does. The result implies budgetary accounting information that represents service performance is beneficial for gaining votes. The limitation that should be considered is the emphasis on the assumption of voter rationality, in which the voters accumulate performance information on the incumbents for their voting decisions. It is highly improbable that voters will allocate time to collecting and reading government financial statements on purpose.